Diseño de un sistema de monitoreo y control para casa habitación basado en DTMF y WEB - Gómez Figueroa, Silvia Liliana; Medina Jiménez, Jorge; Muñoz Sánchez, Daniel Jonathan; Núñez Villaluz, Pablo; Pérez González, Jorge (My University, 2012)
Diseño de un sistema de monitoreo y control para casa habitación basado en DTMF y WEB
Diseño de un sistema de monitoreo y control para casa habitación basado en DTMF y WEB
Keywords: Diseño de un sistema de monitoreo y control para casa habitación basado en DTMF y WEB